Traces of socialism in Burkina Faso's party system : the trajectory of Sankarism in times of political liberalization - Stroh, Alexander (Canadian Journal of African Studies, 2021)
The leftist traces of Thomas Sankara, Africa’s Che, in Burkina Faso and beyond is undeniable. The recent insurgency that overthrew Blaise Compaoré and his long-standing government framed itself as a second revolution, referring extensively to Sankara, whose image proved to mobilize many young protesters. Political parties that identify as Sankarist have opposed Compaoré over decades and managed not to fade away despite the increasing temporal distance from the first revolution led by Sankara between 1983 and 1987. This contribution argues that Sankarism survived in Burkina Faso’s party system because partial political liberalization allowed Sankarist politicians to compete against Compaoré, and because Sankarism adapted to a changing institutional environment and turned away from socialism to become social democratic by trend. In other words, contingently emerging pockets of liberal democracy have let Sankarism survive.
Keywords: Socialism; Sankarism; party politics; Burkina Faso; ideology